Burden and impacts of chronic hepatitis B infection in rural Senegal: study protocol of a cross-sectional survey in the area of Niakhar (AmBASS ANRS 12356). Issue 7 (17th July 2019) - Coste, Marion; De Sèze, Maëlle; Diallo, Aldiouma; Carrieri, Maria Patrizia; Marcellin, Fabienne; Boyer, Sylvie
Abstract : Introduction: Though Senegal has one of the highest estimated prevalence rates of chronic hepatitis B virus (HBV) infection worldwide, epidemiological data in the general population are lacking and consequences of the infection remain undocumented. The ANRS-12356 AmBASS study aims at evaluating the health and socioeconomic burden of chronic HBV infection at the individual, household and population level. Its specific objectives are (1) to document the epidemiology of chronic HBV infection, including prevalence and risk factors; (2) to assess the acceptability of home-based testing and first clinic visit; (3) to investigate the repercussions of chronic HBV infection on living conditions; and (4) to estimate the public health impact of chronic HBV infection at the population level and the feasibility of a decentralised model of HBV test and treat. Methods and analysis: This multidisciplinary cross-sectional survey includes a twofold data collection: (1) home-based screening using dried blood spot (DBS) sampling and collection of sociodemographic, economic and behavioural data, and (2) additional clinical and biological data collection in chronic HBV carriers at the first clinic visit. The prevalence of chronic HBV infection will be estimated in the general population and in key subgroups. Risk factors for HBV acquisition in children will be explored using case-control analysis. HBV burden will be assessed through comparisons of health and economic outcomes between households affected by the disease versus non-affected households. Last, an economic evaluation will assess costs and health benefits of scaling-up HBV care. Ethics and dissemination: This study was approved by the Senegalese National Ethical Committee for Research in Health, and received authorisation from the Senegalese Ministry of Health and the French Commission on Information Technology and Liberties (Senegalese Protocol Number: SEN17/15). The study results will be presented in peer-review journals, international conferences and at a workshop with national stakeholders in order to contribute to the design of programmes to address the HBV pandemic. Trial registration number: NCT03215732 ; Pre-results.